2017
DOI: 10.1051/shsconf/20173409001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Board of Directors in the Establishment of Risk Management Committee

Abstract: The objective of the study is to discuss the roles of board of directors in the establishment of risk management committee for Malaysian's public listed companies. In Malaysia, based on the Malaysian Code on Corporate Governance (MCCG), (2007; 2012) clearly stated the role and responsibility of the board of directors toward the risk management activities. At the Corporate Governance Week 2010 and 2011 as well, the chairman of the Security Commission Malaysia highlighted the responsibility of the board of direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The role of risk management function is to identify business threat and opportunities. This function is expected to help the companies make sound business decisions by incorporating the level of risk that they are willing to accept and execute necessary action to achieve business objectives (Ishak & Mohamad Nor, 2017). In realizing the intended outcome of MCCG 2017, it is important to have effective risk management framework to help the companies to take preventive action on the business threats such as fraud.…”
Section: Critical Analysis On Governance Issues In Fraud Risk Managemmentioning
confidence: 99%
“…The role of risk management function is to identify business threat and opportunities. This function is expected to help the companies make sound business decisions by incorporating the level of risk that they are willing to accept and execute necessary action to achieve business objectives (Ishak & Mohamad Nor, 2017). In realizing the intended outcome of MCCG 2017, it is important to have effective risk management framework to help the companies to take preventive action on the business threats such as fraud.…”
Section: Critical Analysis On Governance Issues In Fraud Risk Managemmentioning
confidence: 99%
“…Nevertheless, while regulators are concerned with the implementation of risk management practices, studies showed that risk management practices are still lacking (Ishak and Mohamad Nor, 2017). Many studies were done to relate risk management practices with cash flow volatility (Lobo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while regulators are concerned with the implementation of risk management practices, studies showed that risk management practices are still lacking (Ishak and Mohamad Nor, 2017). Many studies were done to relate risk management practices with cash flow volatility (Lobo et al, 2019), value creation (Dilling and Harris, 2018), financial crisis (Gonidakis et al, 2020), auditing (Johnstone and Bedard, 2003;White et al, 2020) and taxation (Doyle et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation